(untitled) (Research, Society and Development, 2021)
Objective: To observe the repercussions caused by depression during the gestational period, in an embryonic context, pointing out the main physical, hormonal and psychological changes caused by depression during and after pregnancy with the fetus. Methodology: A bibliographic survey of 30 relevant original publications on the subject was carried out, using the descriptors: Depression; Fetal and Embryonic Development; Gestation; Fetus, in the Scielo, Google Scholar and PUBMED databases. Inclusion and exclusion criteria of articles were used, totaling 23 publications used for the writing of the text. Results and discussion: Severe depression (PD) is a disease that affects about 300 million people worldwide and, during pregnancy, there is the presence of psychobiological and physiological effects on the female body and mind. These changes, together with the depression process lead to a psychopathological condition that directly affects the development of pregnancy, detaining the ability to cause changes in fetal development, associated with high risks for miscarriages, premature births and low birth weight, in addition , even after birth, long-term behavioral and emotional problems may be present. Final Considerations: Untreated depression during the gestational period is associated with risks for the mother and fetus, which can lead to situations of miscarriage or premature birth and impairment of fetal development and problems during adulthood. We also emphasize the need to carry out studies in in vivo and in vitro models for the dissemination of relatively safe data.